Strategi Pengembangan Ekonomi Kreatif yang Inklusif dan Berkelanjutan di Kabupaten Sikka - Masri, Marius (JDEP (Jurnal Dinamika Ekonomi Pembangunan), 2025)
This paper presents a strategic study on the development of an inclusive and sustainable creative economy in Sikka Regency, aiming to identify the potential and challenges in implementing creative economy development policies. The background of this research is driven by the urgent need to enhance the role of the creative economy sector as a driver of local economic growth and the lack of comprehensive studies on integrating inclusivity and sustainability aspects. The novelty of this research lies in its multidimensional approach, combining economic, social, and cultural analyses, which have not been extensively explored before. The research methodology includes literature studies, in-depth interviews with industry stakeholders, and secondary data analysis from relevant institutions. The findings indicate that inclusive strategies encourage community participation and innovation while contributing to regional economic growth. The conclusion highlights the importance of stakeholder collaboration in implementing adaptive policies. This study provides strategic directions for regional creative economy development. The findings offer an empirical foundation for formulating innovative policies to optimize the role of the creative economy in sustainable development at both regional and national levels.